Fish herbivory as key ecological function in a heavily degraded coral reef system. (15th May 2015) - Plass‐Johnson, Jeremiah G.; Ferse, Sebastian C. A.; Jompa, Jamaluddin; Wild, Christian; Teichberg, Mirta
Abstract Localized impacts, such as eutrophication and overfishing, have been identified as major threats to reefs worldwide, resulting in changes in coral reef community composition, from coral‐dominance to algal‐dominance. Herbivory by fishes is frequently cited as a key process structuring benthic community response to stressors. Here, we experimentally tested the capacity of herbivorous fishes to remove macroalgae along an onshore–offshore spatial gradient in the Spermonde Archipelago, Indonesia; a coral reef system exposed to long‐term anthropogenic disturbances. Bioassays of Sargassum and Padina spp. were collected from the reef flat and transplanted onto the reef slope at five islands varying in distance (1–55 km) from the coastline and city of Makassar, South Sulawesi. Supplementary underwater video deployment and fish surveys were used to identify species‐specific differences in herbivore communities and rates of algal removal. Over a 24 h period, Padina was almost completely removed from the two outermost islands, but removal declined toward shore. With the exception of the site closest to Makassar, more than 50% of all transplanted macroalgae were removed. Species diversity of algal‐consuming fishes and total bites increased toward off‐shore, with only one species, Siganus virgatus (Siganidae), feeding at all sites. These changes in herbivore communities underline the capacity for functional resilience under varying levels of reef degradation. Our results exemplify the complexities of ecological functioning along environmental gradients.